Knowledge Equity and Open Science in qualitative research – Practical research considerations - Steinhardt, Isabel; Kruschick, Felicitas (Research Ideas and Outcomes)
How can Knowledge In/Equity be addressed in qualitative research by taking the idea of Open Science into account? Two projects from the Open Science Fellows Programme by Wikimedia Deutschland will be used to illustrate how Open Science practices can succeed in qualitative research, thereby reducing In/Equity. In this context, In/Equity is considered as a fair and equal representation of people, their knowledge and insights and comprehends questions about how epistemic, structural, institutional and personal biases generate and shape knowledge as guidance. Three questions guide this approach: firstly, what do we understand by In/Equity in the context of knowledge production in these projects? Secondly, who will be involved in knowledge generation and to what extent will they be valued or unvalued? Thirdly, how can data be made accessible for re-use to enable true participation and sharing?
Keywords: Open Science; Knowledge Equity; Qualitative Methods

Die (Un-)Sichtbarkeit von (offenen) Bildungsmaterialien in der Soziologie - Hiebl, Johannes; Steinhardt, Isabel; Bigos, Michael (die hochschule)
Der Beitrag beschäftigt sich mit dem Gebrauch von sogenannten Open Educational Resources (OER) innerhalb der deutschsprachigen Soziologie. OER sind Lehr-und Lernmaterialien, die öffent-lich und frei von Kosten zugänglich sind sowie unter einer offenen Lizenz stehen, die es erlaubt, das Material frei zu nutzen, zu vervielfältigen und zu bearbeiten. Um diese Form der Bereitstellung von Lehr-und Lernmaterial zu fördern, sind im deutschen Sprachraum in den letzten Jahren verschie-dene digitale Infrastrukturen entstanden, die an einzelnen Hochschulstandorten, aber auch hochschulübergreifend Lehrenden zur Verfügung stehen, um dort ihr Material zu veröffentlichen. Es wurden 37 dieser Repositorien untersucht. Darüber hinaus wurde auch die Videoplattform YouTube nach soziologischem Lehr-und Lernmaterial durchforstet. Der Beitrag stellt den Zeitverlauf und die Akteur:innen der OER-Veröffentlichungen dar. Anschließend soll mithilfe eines praxistheoretischen Vokabulars die Lehre innerhalb der Soziologie aufgeschlüsselt und ein möglicher Bezug zu den empirischen Ergebnissen hergestellt werden.
Keywords: Soziologie; Praxistheorie; Repositorien; Open Educational Resources; OER

Dem eigenen Anspruch auf der Spur - Ternes, Doris; Bernhard, Nadine; Gewinner, Irina; Goller, Antje; Lohner, David; König, Karsten; Röwert, Ronny; Steinhardt, Isabel; Thielsch, Angelika (Hochschulen in der Pandemie. Impulse für eine nachhaltige Entwicklung von Studium und Lehre)
Der Beitrag geht der Frage nach, welchen Herausforderungen Lehrende durch die digitale Lehre im ersten Corona-Semester 2020 begegnet sind und welche Strategien sie für deren Bewältigung gewählt haben. Als Datengrundlage dienendazu sechs autoethnographische Stories, entstanden im Projekt AEDiL. Diese haben sich als wertvolles Material erwiesen, um unmittelbare Einblicke in das Lehrhandeln und die -planung zu erhalten und die weiterführende Analyse zu ermöglichen. Dabei offenbarte sich der gemeinsame Anspruch der studierenden-zentrierten Lehre als wiederkehrendes Muster. Die mehrstufige Analyse legt offen, wie Lehrpersonen mit den Themen Beziehungsaufbau, Schaffung eines (digitalen) Raums sowie Sicherheit für Studierende umgehen und sich daraus Handlungsmuster entwickeln.

Editorial: Anschaulichkeit – Wissen. Macht. Alternativen. - Eckel, Julia; Linseisen, Elisa (Rabbit Eye – Zeitschrift für Filmforschung)
Keywords: Anschaulichkeit; Anschauung; Film; Epistemologie audiovisueller Medien; Erklärbarkeit; Anschauen; Sichtbarkeit; Unsichtbarkeit

Rabbit Eye: Anschaulichkeit (Rabbit Eye - Zeitschrift für Filmforschung)

Nano-FTIR and chemical force analysis of electrografted aryldiazonium salts on ODT-microcontact printed Au-surfaces - Su, Jiangling; González Orive, Alejandro; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; de los Arcos, T.; Kollmann, S.; Carlet, M. (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Thin Organic‐Inorganic Anti‐Fouling Hybrid‐Films for Microreactor Components - Neßlinger, Vanessa; Welzel, Stefan; Rieker, Florian; Meinderink, Dennis; Nieken, Ulrich; Grundmeier, Guido (Macromolecular Reaction Engineering)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Calibration of 3D scan trajectories for an industrial computed tomography setup with 6-DOF object manipulator system using a single sphere - Butzhammer, Lorenz; Müller, Andreas Michael; Hausotte, Tino (Measurement Science and Technology)
In industrial x-ray computed tomography (CT), the application of more complex scan paths in comparison to the typical circular trajectory (${360}^{°}$ rotation of the measurement object) can extend the potential of CT. One way to enable such 3D scan trajectories is to use a 6-degrees-of-freedom (DOF) object manipulator system. In our case, a hexapod is mounted on top of the rotary table of a commercial CT scanner. This allows for adaptive tilting of the measurement object during the scan. For high accuracy, the geometry calibration of such setups is typically done using the x-ray projections of a calibrated multi-sphere object. Contrary to this, here, we demonstrate a procedure that is based on only a single sphere and can therefore experimentally be implemented with low effort. Using the intrinsic geometry parameters of the CT device as prior information, the hexapod coordinate system with respect to the CT machine coordinate system is determined by means of a one-step optimization approach. The resulting parameters are used to calculate projection matrices that enable the volume reconstruction for 3D scan trajectories. The method is validated using simulated x-ray images and experimental investigations including dimensional measurements. For the used setup, geometric measurement results for 3D scan trajectories that are calibrated with the presented method show in sum increased errors compared to the circular scans. A limited pose accuracy of the manipulator system is discussed as a potential cause. The results nevertheless indicate that the presented method is generally feasible for dimensional CT measurements provided that the pose accuracy is sufficient. The calibration procedure can therefore be a low-cost and easier to implement alternative compared to trajectory calibration methods based on multi-sphere objects, but with a tendency towards lower measurement accuracy. The methodology can in principle be transferred to different setups with 6-DOF manipulator systems, e.g. C-arm CT devices with a robot arm.
Keywords: Applied Mathematics; Instrumentation; Engineering (miscellaneous)

Remote epitaxy of In(x)Ga(1-x)As(001) on graphene covered GaAs(001) substrates - Henksmeier, Tobias; Schulz, Johann Friedemann; Kluth, Elias; Feneberg, Martin; Goldhahn, Rüdiger; Sanchez, Ana M.; Voigt, Markus; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)

Bridging HPC Communities through the Julia Programming Language - Churavy, Valentin; Godoy, William F; Bauer, Carsten; Ranocha, Hendrik; Schlottke-Lakemper, Michael; Räss, Ludovic; Blaschke, Johannes; Giordano, Mosè; Schnetter, Erik; Omlin, Samuel; Vetter, Jeffrey S; Edelman, Alan
The Julia programming language has evolved into a modern alternative to fill existing gaps in scientific computing and data science applications. Julia leverages a unified and coordinated single-language and ecosystem paradigm and has a proven track record of achieving high performance without sacrificing user productivity. These aspects make Julia a viable alternative to high-performance computing's (HPC's) existing and increasingly costly many-body workflow composition strategy in which traditional HPC languages (e.g., Fortran, C, C++) are used for simulations, and higher-level languages (e.g., Python, R, MATLAB) are used for data analysis and interactive computing. Julia's rapid growth in language capabilities, package ecosystem, and community make it a promising universal language for HPC. This paper presents the views of a multidisciplinary group of researchers from academia, government, and industry that advocate for an HPC software development paradigm that emphasizes developer productivity, workflow portability, and low barriers for entry. We believe that the Julia programming language, its ecosystem, and its community provide modern and powerful capabilities that enable this group's objectives. Crucially, we believe that Julia can provide a feasible and less costly approach to programming scientific applications and workflows that target HPC facilities. In this work, we examine the current practice and role of Julia as a common, end-to-end programming model to address major challenges in scientific reproducibility, data-driven AI/machine learning, co-design and workflows, scalability and performance portability in heterogeneous computing, network communication, data management, and community education. As a result, the diversification of current investments to fulfill the needs of the upcoming decade is crucial as more supercomputing centers prepare for the exascale era.

Accessibility properties of abnormal geodesics in optimal control illustrated by two case studies - Bonnard, Bernard; Rouot, Jérémy; Wembe Moafo, Boris Edgar (Mathematical Control and Related Fields)
Keywords: Applied Mathematics; Control and Optimization; General Medicine

Abnormal geodesics in 2D-Zermelo navigation problems in the case of revolution and the fan shape of the small time balls - Bonnard, B.; Cots, O.; Gergaud, J.; Wembe Moafo, Boris Edgar (Systems & Control Letters)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; General Computer Science; Control and Systems Engineering

Frontal theta power increases during table tennis play – indications for neurophysiological demands during open-skill sports? - Büchel, Daniel; Visser, Anton; Lehmann, Tim; Baumeister, Jochen

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen

Engaging with self-tracking applications: how do users respond to their performance data? - Constantiou, Ioanna; Mukkamala, Alivelu; Sjöklint, Mimmi; Trier, Matthias (European Journal of Information Systems)
Keywords: Library and Information Sciences; Information Systems

Model droplet formation in extensional filament stretching within a Filament Extension Atomizer - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim (Rheologica Acta)
Abstract Further innovation in the field of selective laser sintering (SLS) is strongly connected to the availability of new materials since the market is dominated by polyamide 12 (>90%). The aim of this publication is to develop a descriptive model for the droplet formation process in a Filament Extension Atomizer to predict the applicability to exploit further polymers for the SLS process. The feasibility was tested, investigated and characterized using a “Dripping out of a nozzle” setup for uniaxial extension. The droplet formation process was then observed via high-speed camera imaging and classified for certain parameters. The experiments were carried out using semi-diluted polyethylene oxide (600–4000 kg/mol), glycerol and water solutions as model fluids. Driven by the Plateau-Rayleigh instability, different types of spherical droplets were observed and various droplet formation mechanisms demonstrated and analyzed. Based on the experimental results, a predictive model is derived to describe various essential parameters.
Keywords: Rheology; SLS; Lasersintering; exensional rheology

Language in the Age of Mechanical Reproduction - Thomas, Sven (Technology and Language)

Experimental Investigation of the Pressure Dependence of Iso-Octane Combustion - Shaqiri, S.; Kaczmarek, D.; vom Lehn, F.; Beeckmann, J.; Pitsch, H.; Kasper, Tina (Frontiers in Energy Research)
Iso-octane is frequently used as a surrogate fuel or as a component in primary reference fuel blends when low-temperature combustion strategies in engines are investigated. To develop control strategies for these engines, the reaction kinetics of iso-octane must be known starting from the low temperatures and intermediate pressures before ignition to the high temperatures and pressures of combustion. This work adds new experimental data sets to the validation data for reaction mechanism development by investigating the oxidation of iso-octane in stoichiometric mixtures in a flow reactor at pressures of p = 1, 10, and 20 bar and 473K ≤ T ≤ 973 K. The experimental data are compared to simulations with recent reaction mechanisms [Atef et al., Combustion and Flame 178, (2017), Bagheri et al., Combustion and Flame 212, (2020), Cai et al., Proceedings of the Combustion Institute 37, (2018), Fang et al., Combustion and Flame 214, (2020)]. The comparison between experimental and simulated mole fractions as function of temperature show reasonable agreement for all investigated pressures. In particular, the experimentally observed onset of low-temperature reactivity above a certain pressure, the shift of the negative temperature coefficient (NTC) regime with increasing pressure to higher temperatures, and the acceleration of the high-temperature chemistry are captured well in the simulations. Deviations between experimental and simulated results are discussed in detail for the reactivity of iso-octane and some key intermediates such as 2,2,4,4-tetramethyl-tetrahydrofuran, iso-butene and acetone at low temperatures.
Keywords: Economics and Econometrics; Energy Engineering and Power Technology; Fuel Technology; Renewable Energy; Sustainability and the Environment

Nitrous acid in high-pressure oxidation of CH4 doped with nitric oxide: Challenges in the isomer-selective detection and quantification of an elusive intermediate - Hoener, Martin; Kasper, Tina (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Experimental and kinetic modeling study of the positive ions in premixed ethylene flames over a range of equivalence ratios - Knyazkov, Denis A.; Cherepanov, Andrey V.; Kiselev, Vitaly G.; Gerasimov, Ilya E.; Kasper, Tina; Shmakov, Andrey G. (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Directional dependence of the mechanical properties of structural adhesive joints with curing-induced pre-deformations - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part D: Journal of Automobile Engineering)
Owing to the implementation of multi-material construction methods in modern lightweight construction and the associated use of adhesive bonding technology, thermally induced relative displacements of the joining partners occur during the curing process. The resulting extremely complex thermo-chemo-mechanical stresses can influence the properties of the adhesive layers and reduce the load-bearing capacity. In this study, experiments are conducted to examine the influence of process-related thermal relative displacements on the mechanical properties of adhesives. The results show an anisotropy of the mechanical properties of the pre-deformed adhesive layers, depending on the magnitude and direction of the relative displacement.
Keywords: Mechanical Engineering; Aerospace Engineering

Activation effect of ozone and DME on the partial oxidation of natural gas surrogates and validation of pressure-dependent ozone decomposition - Kaczmarek, D.; Bierkandt, T.; Rudolph, C.; Grimm, S.; Shaqiri, S.; Höner, M.; Gaiser, N.; Atakan, B.; Köhler, M.; Hemberger, P.; Kasper, Tina (Applications in Energy and Combustion Science)
Keywords: Fuel Technology; Energy (miscellaneous); Chemical Engineering (miscellaneous)

Kinetic investigation of the ozone-assisted partial oxidation of fuel-rich natural gas mixtures at elevated pressure - Kaczmarek, Dennis; Rudolph, Charlotte; Atakan, Burak; Kasper, Tina (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

A combustion chemistry study of tetramethylethylene in a laminar premixed low-pressure hydrogen flame - Bierkandt, Thomas; Hemberger, Patrick; Oßwald, Patrick; Gaiser, Nina; Hoener, Martin; Krüger, Dominik; Kasper, Tina; Köhler, Markus (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Functionality Study of an Optical Measurement Concept for Local Force Signal Determination in High Strain Rate Tensile Tests - Böhnke, Max; Unruh, Eduard; Sell, Stanislaw; Bobbert, Mathias; Hein, David; Meschut, Gerson (Key Engineering Materials)
Many mechanical material properties show a dependence on the strain rate, e.g. yield stress or elongation at fracture. The quantitative description of the material behavior under dynamic loading is of major importance for the evaluation of crash safety. This is carried out using numerical methods and requires characteristic values for the materials used. For the standardized determination of dynamic characteristic values in sheet metal materials, tensile tests performed according to the guideline from [1]. A particular challenge in dynamic tensile tests is the force measurement during the test. For this purpose, strain gauges are attached on each specimen, wired to the measuring equipment and calibrated. This is a common way to determine a force signal that is as low in vibration and as free of bending moments as possible. The preparation effort for the used strain gauges are enormous. For these reasons, an optical method to determine the force by strain measurement using DIC is presented. The experiments are carried out on a high speed tensile testing system. In combioantion with a 3D DIC high speed system for optical strain measurement. The elastic deformation of the specimen in the dynamometric section is measured using strain gauges and the optical method. The measured signals are then compared to validate the presented method. The investigations are conducted using the dual phase steel material HCT590X and the aluminum material EN AW-6014 T4. Strain rates of up to 240 s-1 are investigated.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Development of a Modified Punch Test for Investigating the Failure Behavior in Sheet Metal Materials - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (The Minerals, Metals & Materials Series)

Experimental and numerical investigation of the influence of multiaxial loading conditions on the failure behavior of clinched joints - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)

A Comprehensive Study on Face Recognition Biases Beyond Demographics - Terhörst, Philipp; Kolf, Jan Niklas; Huber, Marco; Kirchbuchner, Florian; Damer, Naser; Moreno, Aythami Morales; Fierrez, Julian; Kuijper, Arjan (IEEE Transactions on Technology and Society)

Verification of Sitter Identity Across Historical Portrait Paintings by Confidence-aware Face Recognition - Huber, Marco; Terhörst, Philipp; Luu, Anh Thi; Kirchbuchner, Florian; Damer, Naser (26th International Conference on Pattern Recognition, ICPR 2022, Montreal, QC, Canada, August 21-25, 2022)

An Attack on Facial Soft-Biometric Privacy Enhancement - Roig, Dailé Osorio; Rathgeb, Christian; Drozdowski, Pawel; Terhörst, Philipp; Struc, Vitomir; Busch, Christoph (IEEE Trans. Biom. Behav. Identity Sci.)

Development of operational and demand-oriented firefighting equipment - Hanses, Hendrik; Horwath, Ilona (Materials Today: Proceedings)
Keywords: General Medicine

Luna, Laureano. “Strengthening the Russellian Argument Against Abolutely Unrestricted Quantification”. Synthese 200 (2022), No. 3, Paper No. 182, 13 pp - Peckhaus, Volker (Mathematical Reviews)

Does private firms’ disclosure affect public peers’ information environment? - Beyer, Bianca; Flagmeier, Vanessa; Kosi, Urska

Testing, modelling, and parameter identification for adhesively bonded joints under the influence of temperature - Schmelzle, Lars; Striewe, Marius; Mergheim, Julia; Meschut, Gerson; Possart, Gunnar; Teutenberg, Dominik; Hein, David; Steinmann, Paul (Journal of Adhesion Science and Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Robotergestütztes manuelles mechanisches Fügen – RoboterFügen - Neumann, Stefan; Meschut, Gerson; Schmatz, Frederik; Flügge, Wilko

Von der Präsenz-Blockveranstaltung zum Blended Learning-Konzept - Graefe, Grit; Temmen, Katrin (Hochschullehre erforschen)

Applying XAI to an AI-based system for candidate management to mitigate bias and discrimination in hiring - Hofeditz, Lennart; Clausen, Sünje; Rieß, Alexander; Mirbabaie, Milad; Stieglitz, Stefan (Electronic Markets (ELMA))
Abstract Assuming that potential biases of Artificial Intelligence (AI)-based systems can be identified and controlled for (e.g., by providing high quality training data), employing such systems to augment human resource (HR)-decision makers in candidate selection provides an opportunity to make selection processes more objective. However, as the final hiring decision is likely to remain with humans, prevalent human biases could still cause discrimination. This work investigates the impact of an AI-based system’s candidate recommendations on humans’ hiring decisions and how this relation could be moderated by an Explainable AI (XAI) approach. We used a self-developed platform and conducted an online experiment with 194 participants. Our quantitative and qualitative findings suggest that the recommendations of an AI-based system can reduce discrimination against older and female candidates but appear to cause fewer selections of foreign-race candidates. Contrary to our expectations, the same XAI approach moderated these effects differently depending on the context.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

The Investigator’s Dilemma - A Review of Social Media Analytics Research Ethics in Information Systems - Marx, Julian; Mirbabaie, Milad (Australasian Journal of Information Systems)
Social media have become not only integral parts of our private and professional lives, but also an indispensable source of data for empirical research across a variety of academic disciplines. Applying a Social Media Analytics (SMA) methodology, however, imposes heavy ethical challenges on researchers. Scholars in the Information Systems (IS) discipline must deal with a patchwork of ethical frameworks, regulations, and (missing) institutional support. To initiate a debate on how to develop a common understanding of SMA research ethics, this paper compiles a scoping review of extant literature and suggests a research agenda for IS scholarship on this matter. The review yields a total of eight fundamental principles of ethical SMA research, which provide a starting point to guiding individual researchers towards more ethical conduct. At the same time, this work unearths a multitude of intricate dilemmas that are currently unresolved. The findings of this review will encourage IS scholarship to find its own voice in the debate about social media research ethics.
Keywords: Information Systems and Management; Human-Computer Interaction; Business; Management and Accounting (miscellaneous); Information Systems

How crises are different - Design principles for conversational agents to support Emergency Management Agencies - Stieglitz, Stefan; Hofeditz, Lennart; Brünker, Felix; Ehnis, Christian; Mirbabaie, Milad; Ross, Björn (International Journal of Information Management)
Keywords: Library and Information Sciences; Computer Networks and Communications; Information Systems

Ethics and AI in Information Systems Research - Mirbabaie, Milad; Brendel, Alfred B.; Hofeditz, Lennart (Communications of the Association for Information Systems)
Keywords: Information Systems

Catchword: Digital Detox - Mirbabaie, Milad; Stieglitz, Stefan; Marx, Julian (Business & Information Systems Engineering)
Keywords: Information Systems

Review of Design-Oriented Green Information Systems Research - Brendel, Alfred Benedikt; Chasin, Friedrich; Mirbabaie, Milad; Riehle, Dennis M.; Harnischmacher, Christine (Sustainability)
Green IS (GIS) research addresses environmental challenges brought on by climate change and the need to preserve the natural environment. Within this scope, design-oriented research, most notably within the Design Science Research (DSR) community, aims to provide solutions to these environmental challenges in the form of novel artifacts. The resulting IS solutions are valuable instruments for reducing emissions, increasing energy efficiency, and mitigating waste. Over the past 14 years, the IS research community was called upon multiple times to focus on designing solutions suitable for facilitating sustainability. However, it is unclear how these calls for action resonated within the design-oriented research community. Against this background, we analyzed the landscape of design-oriented GIS research by looking at 60 different GIS studies that have designed and evaluated an artifact. By analyzing these publications, we were able to make six observations. Based on these observations, we discuss how design-oriented GIS research can evolve to live up to the expectations of creating an immediate positive environmental impact.
Keywords: Management; Monitoring; Policy and Law; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

Click me…! The influence of clickbait on user engagement in social media and the role of digital nudging - Jung, Anna-Katharina; Stieglitz, Stefan; Kissmer, Tobias; Mirbabaie, Milad; Kroll, Tobias (PLOS ONE)
Clickbait to make people click on a linked article is commonly used on social media. We analyze the impact of clickbait on user interaction on Facebook in the form of liking, sharing and commenting. For this, we use a data set of more than 4,400 Facebook posts from 10 different news sources to analyze how clickbait in post headlines and in post text influences user engagement. The results of our study revealed that certain features (e.g., unusual punctuation and common clickbait phrases) increase user interaction, whereas others decrease engagement with Facebook posts. We further use our results to discuss the potential role of digital nudging in the context of clickbait. Our results contribute to understanding and making use of the effect of different framings in social media.
Keywords: Multidisciplinary

Rumor Correction in Social Media Crisis Communication: A Case of Connective Sense-Breaking - Mirbabaie, Milad; Marx, Julian; Reimann, Annette (AIS Transactions on Human-Computer Interaction)
Keywords: General Medicine

How News Websites Refer to Twitter: A Content Analysis of Twitter Sources in Journalism - Kapidzic, Sanja; Neuberger, Christoph; Frey, Felix; Stieglitz, Stefan; Mirbabaie, Milad (Journalism Studies)
Keywords: Communication

Trust Me, I’m an Influencer! - A Comparison of Perceived Trust in Human and Virtual Influencers - Hofeditz, Lennart; Nissen, Anika; Schütte, Reinhard; Mirbabaie, Milad (30th European Conference on Information Systems - New Horizons in Digitally United Societies, ECIS 2022, Timisoara, Romania, June 18-24, 2022)

A Design Science Artefact for Cyber Threat Detection and Actor Specific Communication - Eyilmez, Kaan; Basyurt, Ali Sercan; Stieglitz, Stefan; Fuchss, Christoph; Kaufhold, Marc-André; Reuter, Christian; Mirbabaie, Milad (Australasian Conference on Information Systems (ACIS))
Keywords: Student; Security; Projekt-CYWARN

Automating Crisis Communication in Public Institutions–Towards Ethical Conversational Agents That Support Trust Management - Hofeditz, Lennart; Mirbabaie, Milad; Erle, Lukas; Knoßalla, Eileen; Timm, Lara (Proceedings of the 17th International Conference on Wirtschaftsinformatik)

Credibility of Cyber Threat Communication on Twitter–Expert Evaluation of Indicators for Automated Credibility Assessment - Basyurt, Ali Sercan; Fromm, Jennifer; Stieglitz, Stefan; Mirbabaie, Milad (Proceedings of the 17th International Conference on Wirtschaftsinformatik)

From Dark Patterns to Digital Sludging–Mapping the Ethical Debate on Controversial Persuasive System Design - Clausen, Sünje; Marx, Julian; Mirbabaie, Milad; Stieglitz, Stefan (Proceedings of the 43rd International Conference on Information Systems (ICIS))

Knowledge Work ‘Unplugged’-Digital Detox Effects on ICT Demands, Job Performance and Satisfaction - Mirbabaie, Milad; Braun, Lea-Marie; Marx, Julian (Proceedings of the 17th International Conference on Wirtschaftsinformatik)

Motivators of Knowledge Workers to Conduct Digital Detox - Marx, Julian; Braun, Lea Marie; Mirbabaie, Milad (Proceedings of the 43rd In the Proceedings of the 43rd International Conference on Information Systems (ICIS))

‘Botfluencers’–The Impact of Social Bot Awareness and User Personality on Brand Opinion Formation - Brünker, Felix; Marx, Julian; Mirbabaie, Milad; Stieglitz, Stefan (Proceedings of the Australasian Conference on Information Systems (forthcoming))

Working with ELSA – How an Emotional Support Agent Builds Trust in Virtual Teams - Hofeditz, Lennart; Harbring, Mareen; Mirbabaie, Milad; Stieglitz, Stefan (Proceedings of the Annual Hawaii International Conference on System Sciences)

SMART-Portal: A data tracking tool for research purposes from social media and news websites - Stieglitz, Stefan; Basyurt, Ali; Mirbabaie, Milad (Proceedings of the Annual Hawaii International Conference on System Sciences)

Oiling the ’Tireless Selling-Machine’ - Exploring Requirements for the Deployment of Social Bots in Social Commerce - Brünker, Felix; Marx, Julian; Mirbabaie, Milad; Stieglitz, Stefan (55th Hawaii International Conference on System Sciences, HICSS 2022, Virtual Event / Maui, Hawaii, USA, January 4-7, 2022)

Help Wanted-Challenges in Data Collection, Analysis and Communication of Cyber Threats in Security Operation Centers - Basyurt, Ali Sercan; Fromm, Jennifer; Kuehn, Philipp; Kaufhold, Marc-André; Mirbabaie, Milad (Proceedings of the 17th International Conference on Wirtschaftsinformatik)

Ethics Guidelines for Using AI-based Algorithms in Recruiting: Learnings from a Systematic Literature Review. - Hofeditz, Lennart; Mirbabaie, Milad; Luther, Audrey; Mauth, Riccarda; Rentemeister, Ina (HICSS)

Man nehme... den Konjunktiv. Verbformen in Kochrezepten - Wallmeier, Nadine (Praxis Deutsch)

„Alles Leben ist Problemlösen“ (Popper) – Die Komplexität der alltäglichen Lebensführung erfassen durch Problembasiertes Lernen - Bigga, Regine; Raacke, Georg (HiBiFo – Haushalt in Bildung & Forschung)
In der Haushaltswissenschaft und der haushaltsbezogenen Bildung besteht eine große Herausforderung darin, Komplexität zu erfassen, zu verstehen und als eine bewältigbare Aufgabe anzunehmen. Problembasiertes Lernen (PBL) bietet ein Konzept, komplexere Frageund Problemstellungen aus der alltäglichen Lebensführung und deren Verwobenheit mit gesellschaftlichen Rahmenbedingungen zu verstehen. Aus hochschuldidaktischer Sicht werden Chancen und Begrenzungen diskutiert.

Ressourcen – Gesundheit zwischen Eigenverantwortung und gesellschaftlicher Verantwortung - Bigga, Regine (HiBiFo – Haushalt in Bildung & Forschung)
Die Herstellung und Aufrechterhaltung von Gesundheit und Wohlergehen wird in vielen Diskursen als alleinige Aufgabe des Individuums angesehen. Die Ressource Gesundheit hängt vom individuellem Verhalten ab, aber auch von gesellschaftlichen Rahmenbedingungen. Es wird der Frage nachgegangen, welche äußeren Bedingungen sich negativ oder positiv auf die Bildung der Ressource Gesundheit auswirken.

Neuronale Netze in der Konstruktion zur Ausschöpfung der Potentiale additiver Fertigungstechnologien - Ott, Manuel; Meihöfener, Niclas; Koch, Rainer (Bericht 407 - 7. Tagung des DVM-Arbeitskreises Additiv gefertigte Bauteile und Strukturen)
Die additive Fertigung bietet die Möglichkeit, digitale Prototypen dank der Besonderheit der werkzeuglosen Fertigung schnellstmöglich in reale Strukturen umzusetzen. Dieses Verfahren kann jedoch nur dann mit optimaler Geschwindigkeit genutzt werden, wenn Engpässe wirksam vermieden werden können. Einer dieser Engpässe ist der Konstruktionsprozess. Gerade im Bereich der additiven Fertigung sind in letzter Zeit immer leistungsfähigere Softwarelösungen erschienen, die das Design für die additive Fertigung, einschließlich der meisten Computer-Aided-Design (CAD)-Aufgaben, beschleunigen. In vielen Bereichen wird daher bereits versucht, so viele Schritte wie möglich zu automatisieren, nicht selten unter Verwendung neuronaler Netze und künstlicher Intelligenz. Dieser Beitrag zeigt am Beispiel einer automatisierten Strukturoptimierung eines Stuhls, warum das Nutzen neuronaler Netze im Konstruktionsprozess sinnvoll ist, um die Bereiche der konventionellen Topologieoptimierung und des Generative Design weiter zu verknüpfen und somit die Produktentwicklungszeit zu reduzieren.
Keywords: Künstliche Intelligenz; Neuronale Netze; 3D-Druck; Design for Additive Manufacturing

The environmental impact on the strain rate dependent energy absorption capability of a hybrid crash absorber element - Haller, Sebastian; Tinkloh, Steffen Rainer; Tröster, Thomas; Brandt, Robert (5th International Conference Hybrid 2022 Material & Structures)

Konturen einer praxistheorethischen Professions- und Entscheidungsforschung - Dahmen, Stephan (Empirische Pädagogik)
Ausgehend von der Problematisierung eines individualistischen Begriffs von Entscheidung referiert der Beitrag eine praxistheoretische Perspektive auf Entscheidungen in pädagogischen Kontexten mit dem Zweck, die Sensitivität für deren empirische Erforschung, insbesondere im Rahmen qualitativ-rekonstruktiver Forschung zu erhöhen. Die praxistheoretische Perspektive auf Soziale Wirklichkeit wird anhand von drei perspektivischen Verschiebungen des Entscheidungsbegriffs diskutiert: Erstens, der Frage der raum-zeitlichen Verortung und Beobachtbarkeit von Entscheidungen, zweitens, der praxistheoretischen Dezentrierung des Entscheidungs- und Handlungssubjekts und drittens, anhand der Frage der Rationalität von Entscheidungen. Der Beitrag argumentiert diesbezüglich für eine analytische Abkehr von präskriptiven Modellen professionellen Entscheidens als reflexiv-intentionale Verknüpfung von Diagnose, Inferenz und Behandlung und plädiert dafür, den Untersuchungsfokus vom individuellen Akteur zum situierten, prozesshaften Vollzug von Handlungen in ausgestatteten, formatierten und vernetzten Situationen zu verschieben.

Toward a Competence Model for Graphical Modeling - Soyka, Chantal; Schaper, Niclas; Bender, Elena; Striewe, Michael; Ullrich, Meike (ACM Transactions on Computing Education)
Modeling is an integral part of many computing-related disciplines and thus also represents a curricular core component in computing education in tertiary education. Competence models in which modeling is integrated at least to some extent already exist in some of these disciplines. However, for the core component of graphical modeling, a competence model that illuminates the relevant competences in detail is still lacking. Therefore, we develop a competence model for graphical modeling with the aim to make teaching and especially assessments in the field more competence-oriented. This paper reports on the first two studies conducted to develop and validate the competence model for graphical modeling. In the first study, the structure of the competence model was developed based on theories and approaches of educational science. Competences relevant for graphical modeling were deductively derived from literature and existing university course descriptions using techniques of qualitative content analysis. The result of the first study is a preliminary competence model. In the second study, the preliminary competence model was reviewed by means of an expert rating in the modeling community. The competence model was revised and refined based on these findings and subsequent expert discussions. The main result of the investigation represents the competence model for graphical modeling (CMGM), which includes a total of 74 competence facets at different cognitive process levels in the five content areas of ”model understanding and interpreting”, ”model building and modifying”, ”values, attitudes, and beliefs”, ”metacognitive knowledge and skills”, and ”social-communicative skills”.
Keywords: graphical modeling; conceptual modeling; computer science; competence model; higher education

Piloteinsatz einer E-Assessment-Plattform für die grafische Modellierung - Ullrich, Meike; Pfeiffer, Peter; Schiefer, Gunther; Soyka, Chantal; Stottrop, Tobias; Striewe, Michael; Fettke, Peter; Loos, Peter; Oberweis, Andreas; Schaper, Niclas (20. Fachtagung Bildungstechnologien (DELFI))

E-Assessment-Plattform für die grafische Modellierung - Ullrich, Meike; Pfeiffer, Peter; Schiefer, Gunther; Soyka, Chantal; Stottrop, Tobias; Striewe, Michael; Fettke, Peter; Loos, Peter; Oberweis, Andreas; Schaper, Niclas (20. Fachtagung Bildungstechnologien (DELFI))

Organisationen als Kompromissmaschinen: Zur Mikrofundierung von Organisationen im Neo-Institutionalismus und der Soziologie der Konventionen am Beispiel Sozialer Hilfen am Übergang von der Schule in den Beruf - Dahmen, Stephan (Steuerung von Bildungseinrichtungen. Theoretische Analysen erziehungswissenschaftlicher Organisationsforschung)

CSR Reporting under the Non-Financial Reporting Directive: Evidence from Non-publicly Listed Firms - Gulenko, Maryna; Kohlhase, Saskia; Kosi, Urska
We examine variation in mandatory CSR reporting practices based on a large sample of non-publicly listed savings banks in Germany. They do not have typical shareholders but rather are established by municipal trustees and can serve clients only in their distinct operating area. This setting permits us to identify demand for CSR information by their main stakeholder groups – municipal trustees and private and corporate clients. In this way, our analysis focuses on the double-materiality approach to CSR reporting. We find that demand for CSR information by supervisory board chairperson belonging to a left-wing or green party and the presence of more supervisory board members belonging to a left-wing or green party are associated with longer CSR reports and more disclosure on environmental, social, employee and human rights matters. In addition, competition for private clients and the sustainability orientation of corporate clients are associated with longer reports and more disclosure on environmental, employee and human rights matters. These findings suggest that savings banks’ CSR reports cater to their principal stakeholders’ demand for CSR information.
Keywords: Corporate social responsibility; Mandatory reporting; Non-publicly listed banks; Double materiality; Stakeholder groups; Political influence

Entwicklung eines Performanztests für das bildungswissenschaftliche Lehramtsstudium: Erfassung von Beratungskompetenz - Wotschel, Philipp

Rollenspiele als Übungs- & Prüfungsformate in der universitären Lehramtsausbildung. - Meier, Jana; Vogelsang, Christoph; Wotschel, Philipp; Janzen, Thomas

Entwicklung eines Performanztests für das bildungswissenschaftliche Lehramtsstudium: Erfassung von Beratungskompetenz - Wotschel, Philipp

Einschätzungen Studierender zu Prüfungsformaten im Lehramtsstudium. - Vogelsang, Christoph; Meier, Jana; Wotschel, Philipp; Janzen, Thomas

Investigation on hot sheet metal forming by means of a longitudinal flux inductor - Pfeifer, Florian; Tröster, Thomas; Marten, Thorsten; Dietrich, André; Nacke, Bernard; Grundmeier, Guido (Proceedings of the 6th International Conference on Steels in Cars and Trucks)

Regionales Sprechen und Schreiben

Techniken und Praktiken der Verdatung - Bender, Michael; Bubenhofer, Noah; Dreesen, Philipp; Georgi, Christopher; Rüdiger, Jan Oliver; Vogel, Friedemann (Diskurse – digital)

Screening zur Erfassung des Leseverständnisses in den Klassen 6 – 7 (SELV 6 – 7) - Seifert, Susanne; Maitz, Katharina; Riedl, Sylvia; Neumaier, Arnold; Stoff, Ilona; Gasteiger-Klicpera, und Barbara (Diagnostica)
Zusammenfassung. Im vorliegenden Beitrag wird das Screening zur Erfassung des Leseverständnisses für die Klassen 6 – 7 (SELV 6 – 7) vorgestellt, welches Leseverständnis während des Lesens mittels der Maze-Prozedur erfasst. Der Test liegt in einer Print- (SELV-P) und Digitalversion (SELV-D) vor. Es wurden 5 Paralleltestformen entwickelt. Zwei Studien zur Überprüfung der Reliabilität und Validität in den Klassen 6 und 7 werden präsentiert, wobei drei verschiedene Maze-Scorings (1: korrekt, 2: korrekt-inkorrekt, 3: korrekt / bearbeitet) einander gegenübergestellt werden. Studie 1 (SELV-P, n = 222, davon 85 6. Klasse) zeigt, dass die 4 Formen (ohne Form 3) die gleiche Fähigkeit messen, jedoch mit unterschiedlichen Mittelwerten. Der Einsatz als Lernverlauf-Messinstrument erscheint somit mit separaten Normen je Form möglich. Die Paralleltest- und Retestreliabilität dieser 4 Formen ist unter Verwendung von Score 1 und 2 ausreichend hoch, nicht aber bei Score 3. In Studie 2 (SELV-D, n = 345, davon 150 6. Klasse) wurde nur Form 1 betrachtet, die unter Verwendung aller 3 Scores die Kriterien der diskriminanten und konvergenten Validität erfüllt.
Keywords: Clinical Psychology

Diagnostik und Differenzierung - Seifert, Susanne; Paleczek, Lisa; Gasteiger-Klicpera, Barbara (Handbuch der sonderpädagogischen Diagnostik. Einführung in die Status- und Prozessdiagnostik sowie Förderplanung)

Vergleich unterschiedlicher Instrumente zur Messung von Gesundheitskompetenz im Zusammenhang mit Lesekompetenz und kognitiven Fähigkeiten von Jugendlichen - Seifert, Susanne; Maitz, Katharina; Pendl, Dominik; Gasteiger-Klicpera, Barbara (Diagnostica)
Zusammenfassung. Instrumente zur Messung von Gesundheitskompetenz bei Jugendlichen basieren auf sehr heterogenen Definitionen und Konzepten. Zudem können sie grundsätzlich in subjektive (Selbsteinschätzungs–) und objektive (die Performanz messende) Verfahren unterteilt werden. In der vorliegenden Studie wurden 2 subjektive (eHEALS; Kurzform des HLS-EU-Q16) und ein objektives Messinstrument (Claim) von 471 Jugendlichen der 6. und 7. Klassenstufe (Durchschnittsalter 13.04 Jahre; 49 % Mädchen; 63 % Familiensprache Deutsch) bearbeitet und auf ihren wechselseitigen Zusammenhang, den Zusammenhang mit kognitiven und Lesefähigkeiten, sowie Unterschiede in Bezug auf Geschlecht und Familiensprache untersucht. Das objektive Verfahren korrelierte nicht mit den subjektiven Verfahren. Dies bestätigt die Annahme, dass sie aufgrund der Messperspektive unterschiedliche Indikatorenausprägungen von Gesundheitskompetenz erfassen. Korrelationen mit Lese- und kognitiven Fähigkeiten zeigten sich nur beim objektiven Instrument, wohingegen die Selbsteinschätzungsinstrumente diese Aspekte der Gesundheitskompetenz nicht abbilden. Unterschiede hinsichtlich des Geschlechts und der Familiensprache zeigten sich insbesondere beim objektiven Instrument, allerdings sind Antwortverzerrungen bei Selbsteinschätzungen möglich. Die spezifischen Vor- und Nachteile von subjektiven und objektiven Verfahren sollten bei der Instrumentenauswahl berücksichtigt werden.
Keywords: Clinical Psychology

Comparing tablet and print mode of a german reading comprehension test in grade 3: Influence of test order, gender and language - Seifert, Susanne; Paleczek, Lisa (International Journal of Educational Research)
Keywords: Education

Comparing Student high and low Reading Performance with Differentiated Digital Reading Materials - Paleczek, Lisa; Ender, Daniela; Kogler, Andrea; Seifert, Susanne (European Conference on e-Learning)
The present study investigates eight Grade-4 classes (9- to 12-year-olds, 52.1% girls) who worked on at least 10 lessons using project RegioDiff material. The study focuses on one of these lessons (including nine text passages and corresponding tasks) and on students with low (19 students, percentile <15) and high reading skills (29 students, percentile > 70). While students were working with the material, screencasts were recorded (30h). The construct “task performance” (processing time, response accuracy, and task engagement) was then analysed using the screencasts.
The analysis revealed that the two groups differed significantly in the processing time of two tasks, but not in the total time spent on all nine tasks. Significant differences were revealed also for general task engagement. Task engagement was highly correlated with processing time. Participants with higher reading skills spent more time on the tasks and were more engaged than participants with lower reading skills. However, we did not find any differences in terms of answer accuracy. This indicates that task difficulty and student reading skills were well matched.
The study also shows how tasks may be adapted or augmented in order to match the learning environment more closely to student learning needs.

Bending and Bowing: How Teachers Adapt a Vocabulary-Based Reading Program to Their Students Needs - Kulmhofer-Bommer, Andrea; Seifert, Susanne; Paleczek, Lisa; Gasteiger-Klicpera, Barbara (Journal of Education)
This paper investigates the implementation of a reading program designed for third grade elementary school classrooms in Austria. Using a mixed-methods approach, lesson types were identified, respective class compositions analyzed, and the effects on students’ reading gains examined. The results show that the lesson types seem to reflect learner group needs as students in the different lesson types profited similarly from the reading program. This supports the hypothesis that reading is a highly individualized process and leads to the conclusion that the instructional approach of the reading program investigated supports teachers in conducting reading lessons tailored to their students’ needs.
Keywords: Education

A feasibility study of digital content use in inclusive, Austrian primary school practice - Paleczek, Lisa; Ender, Daniela; Berger, Jessica; Prinz, Katharina; Seifert, Susanne (International Journal of Educational Research)
Keywords: Education

First-year university students' self-regulated learning during the COVID-19 pandemic: a qualitative longitudinal study - Liebendörfer, Michael; Kempen, Leander; Schukajlow, Stanislaw (ZDM – Mathematics Education)
Abstract When the COVID-19 pandemic began, many universities switched to fully online teaching. This unexpected switching to online teaching was challenging for both teachers and students, and restrictions that were put in place because of pandemic made this challenge even greater. However, new ways of teaching might also open new opportunities for students’ learning. The research question driving our study was as follows: how do students regulate their learning and specifically their choice of resources and peer learning in university mathematics classes that are fully taught online as offered during the COVID-19 pandemic? We report on a longitudinal, qualitative study in which students recorded a brief audio diary twice a week over one whole semester (14 weeks). We focused on three students who completed 70 interviews in total and finished the semester with varying degrees of success. The results show how the students structured their studying (e.g., the roles that deadlines or synchronous teaching events played). They illustrate the strengths and limitations of digital materials provided by the lecturer and the use of complementary media. Further, the pandemic uncovered the double-edged role of simple, often anonymous exchanges (e.g., via Discord servers), with few binding forces for either side, and the significance of stable learning partnerships for students’ success. Our research highlights aspects that should be focal points when comparing traditional instruction and online instruction during the pandemic from a self-regulatory perspective. Practical implications refer to how these aspects can be combined sensibly in fully online courses, but also in blended learning contexts.
Keywords: General Mathematics; Education

Exploring the Perceived Relevance of University Mathematics Studies by First-Semester Teaching Students - Büdenbender-Kuklinski, Christiane; Hochmuth, Reinhard; Liebendörfer, Michael (International Journal of Research in Undergraduate Mathematics Education)
Abstract As earlier research results suggest that many mathematics teaching students criticize a missing relevance in their studies, we explore explanations and interrelationships of their relevance assessments. We aim at finding out how one could support the students in attributing relevance to their study programs. A two-fold model for relevance assessments in mathematics teacher education is proposed, consisting of relevance content and relevance reasons. We investigate students' relevance perceptions of mathematical topics and of topics’ complexities, as well as their rating of individual and societal/ vocational relevance reasons, all in relation to their perception of the relevance of their overall program of study. Contrary to earlier research findings, our results suggest that mathematics teaching students already do attribute relevance to many content areas and that a preparation for the teaching profession is not the only reason for them to assign relevance. There also seem to be many students who would attribute relevance if they could develop as individuals and pursue their interests. We suggest that giving students opportunities to set individual priorities in their studies could hence support their relevance assessments. As low relevance assessments seem to be connected to students’ motivational problems, students might profit from motivational support, as well.
Keywords: Education; Mathematics (miscellaneous)

Noise Processes and Nonlinear Mechanisms in Optoelectronic Phase-Locked Loop Using a Balanced Optical Microwave Phase Detector - Bahmanian, Meysam; Scheytt, J. Christoph (IEEE Transactions on Microwave Theory and Techniques)

Survey on methods for early prototyping and validation of technical product ideas - Asmar, Laban; Grigoryan, Khoren; Kuhn, Arno; Dumitrescu, Roman (2022 IEEE 20th International Conference on Industrial Informatics (INDIN))

Ein Ansatz zur Strukturierung von KI-Assistenzen im Model-Based Systems Engineering - Kaiser, Lydia; Schräder, Elena; Bernijazov, Ruslan; Foullois, Marc; Dumitrescu, Roman (Tag des Systems Engineering)

Professionalitätsentwicklung angehender Lehrkräfte - Kirsch, Alexander

Kooperatives Unterrichten von Studierenden des Lehramts an Grund- und Förderschulen als Vorbereitung auf den inklusiven naturwissenschaftlichen Sachunterricht - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Messung von Unterrichtsplanungskompetenz im Fach Sachunterricht: Empirische Befunde zur Kompetenzentwicklung angehender Grundschullehrkräfte auf Grundlage einer mehrdimensionalen Kompetenzstruktur - Kirsch, Alexander (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im vorliegenden Beitrag werden nach ausführlicher theoretischer Diskussion des Kompetenzbegriffs und der Definition von Kompetenz als Können ein Modell sachunterrichtlicher Planungskompetenz sowie ein daran anschließendes Messinstrument vorgestellt. Im Hinblick auf den Einsatz dieses Instrumentes im Rahmen einer Evaluation des nordrhein-westfälischen Praxissemesters stellen sich Fragen nach der psychometrischen Struktur der Testauswertung. Da das Instrument sowohl zur Testung von Sachunterrichtsstudierenden mit dem Lehramtsprofil ‚Grundschule‘ als auch von Sachunterrichtsstudierenden mit sonderpädagogischem Schwerpunkt eingesetzt werden soll, ist zu zeigen, dass die Testergebnisse nicht durch den gewählten Studiengang beeinflusst werden. Im Beitrag werden Rohdaten aus einer Studie an der Universität Paderborn ( n = 121) genutzt, um eine fünfdimensionale Modellstruktur gegen eine eindimensionale zu testen und empirisch gestützte Argumente für eine mehrdimensionale Skalierung zu generieren. Durch Differential-Item-Functioning-Analysen wird geprüft, ob die Itemschwierigkeiten mit dem Merkmal ‚Studiengang‘ interagieren, sodass sie sich trotz gleicher Kompetenzausprägung für Untersuchungsteilnehmende beider Studierendengruppen signifikant unterscheiden und zu einer diagnostischen Verzerrung führen würden. Abschließend wird der beispielhafte Einsatz des Instrumentes im Rahmen einer Wirksamkeitsanalyse in Bezug die Effektivität des nordrhein-westfälischen Praxissemesters an der Universität Paderborn ( n = 26) dargelegt. Aus den differenzierten Ergebnissen werden unter anderem erste Hinweise auf Defizite in der Lehrerinnen- und Lehrerausbildung abgeleitet.
Keywords: Education

Die Tamagotchisierung des Selbst. Zur Anschaulichkeit von animierten Körperdaten - Schloots, Franziska Margarete (Rabbit Eye - Zeitschrift für Filmforschung)
Keywords: Wearable; selft-tracking; Selbstvermessung; Animation; Tamagotchi; Anschaulichkeit

One-bit target detection in collocated MIMO radar and performance degradation analysis - Xiao, Yu-Hang; Ramirez, David; Schreier, Peter J; Qian, Cheng; Huang, Lei (IEEE Transactions on Vehicular Technology)

Experimental Comparison of FPGA-Implemented Model Predictive Voltage Control to Cascaded Proportional Resonant Control for a Three-Phase Four-Wire Three-Level Grid-Forming Inverter of 250 kVA - Lange, Jarren; Schmies, Dominik; Stille, Karl Stephan Christian; Böcker, Joachim; Wallscheid, Oliver (EPE'22 ECCE Europe)

Adaptive Operating Strategy for Induction Motors Under Changing Electrical-Thermal Conditions - Stender, Marius; Becker, Marius; Wallscheid, Oliver; Böcker, Joachim (48th Annual Conference of the Industrial Electronics Society (IECON))

Texte im Deutschunterricht. - Rezat, Sara (12 Perspektiven auf den Deutschunterricht. Wissenswertes für Deutschlehrkräfte.)

Schreiben - Rezat, Sara (Basiswissen Lehrerbildung: Deutsch unterrichten)

Effects of Teacher Feedback on Primary School Students’ Self-Efficacy Beliefs and their Interest in Science Lessons. Single Paper. ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Stabilization of arbitrary structures in a doubly degenerate reaction-diffusion system modeling bacterial motion on a nutrient-poor agar. - Winkler, Michael (Calculus of Variations and Partial Differential Equations)